Answer:a
Step-by-step explanation:
Answer:
x=3
Step-by-step explanation:
lets take x as the number
so
6(x-3)=x-3
since it says "6 times" we know that we will have to multiply the difference by 6 and it says the difference of a number and 3 is equal to 3 less than the number so we know that we are subtracting 3 from x
6x-18=x-3
6x-x=18-3
5x=15
x=3
Answer:
The numbers are 12 and 3.
Step-by-step explanation:
12+3=15
&
3×12= 36
:)
Answer:
(1, 1 )
Step-by-step explanation:
The solution to a system of equations given graphically is at the point of intersection of the 2 graphs.
Here the point of intersection is at (1, 1 )
Thus the solution to f(x) = g(x) is (1, 1 )